ChemInform Abstract: Microwave‐Assisted Amidation of Arylacetic Acids by Reaction with 2‐Aryl‐ethylamines. Issue 30 (4th July 2013) - Gruen, Alajos; Milen, Matyas; Foeldesi, Tamas; Abranyi‐Balogh, Peter; Drahos, Laszlo; Keglevich, Gyoergy
Abstract 25 examples